Vida cultural, econômica e cotidiano de mulheres africanas em São Paulo : contribuições para a terapia ocupacional - Sato, Miki Takao (2017)
The purpose of this study is to discuss the economic life and daily exchange dynamic of African women living in the city of São Paulo, proposing a discussion of these aspects as meaning production, emancipation, intercultural dialogue and collective actions. The historical overview of migration in the world, in Brazil and São Paulo has always been marked by problems and various challenges. In Brazil, it still rules an authoritarian and restrictive legislation, which does not answer the contemporary demands of migratory phenomena. In São Paulo, a Municipal Politics for Migrant Population has been built by actors from civil society, government and social movements and the migrant community, where they have established new dialogues for these demands. Despite the difficulties and challenges, there are other perspectives and new possibilities that seek a greater dialogue with human rights and citizenship presuppositions. Some of these actions are introduced, as well as an overview of formal and informal institutions and services for the migrant population. São Paulo experiences an important presence of African migration, as well as of African women, especially with some economic activity. This mobility has occurred in several dimensions: study, work, refuge, new opportunities and the African theme assumed in the perspective of this work is a cultural, artistic and intellectual contribution. There is also a growing movement in the city for the appreciation of Afro-Brazilian culture and gender protagonism. When they stay in the city, African women are confronted with this context and seek a dialogue through their gastronomic, cultural, political and esthetics activities. The theoretical contextualization brings reflections of anthropology, ethnography, social occupational therapy, urban anthropology and discussion on economic life. The present work was developed through the ethnographic field research based on observation, interviews and living in everyday situations and work of the interlocutors. The data of the field notebooks resulted in the description of four main narratives and stories of others African women also composed the work, whose women has been a significant presence in the struggle for human rights, gender protagonism and appreciation of artistic contributions to the city. The experiences were presented through an analysis and transversal discussions, permeating reflections with concepts of daily, economic life, activity and culture. The theme of migration has found repercussion in productions in international occupational therapy and in Brazil for years, these are necessary dialogues for the new challenges of the career. The occupational therapist who also dialogues with contemporary issues, with processes of rupture of support networks, and who also proposes new possibilities for life projects, it is one of the professionals called to enter this scenery. One of the main challenges of the work was to produce a reflection on the professional’s role and researcher and their interlocutions between field and research. The reflection on human rights, gender and economic life in migration could built social technologies in occupational therapy to address issues that emerge from social conflicts and from the problems of a society marked by ever-changing inequalities.